Are smokers with acute cough in primary care prescribed antibiotics more often, and to what benefit? An observational study in 13 European countries. - Stanton, N; Hood, K; Kelly, M; Nuttall, J; Gillespie, D; Verheij, T; Little, P; Godycki-Cwirko, M; Goossens, H; Butler, C (2010)
Little is known about actual clinical practice regarding management of smokers compared with ex-smokers and nonsmokers presenting with acute cough in primary care, and whether a lower threshold for prescribing antibiotics benefits smokers. This was a multicentre 13-country European prospective observational study of primary care clinician management of acute cough in consecutive immunocompetent adults presenting with an acute cough of